2004
DOI: 10.1057/palgrave.jors.2601771
|View full text |Cite
|
Sign up to set email alerts
|

Ant colony optimization and local search for bin packing and cutting stock problems

Abstract: The Bin Packing Problem and the Cutting Stock Problem are two related classes of NP-hard combinatorial optimisation problems. Exact solution methods can only be used for very small instances, so for real-world problems we have to rely on heuristic methods. In recent years, researchers have started to apply evolutionary approaches to these problems, including Genetic Algorithms and Evolutionary Programming. In the work presented here, we used an ant colony optimisation (ACO) approach to solve both Bin Packing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 23 publications
(44 reference statements)
2
119
0
8
Order By: Relevance
“…Levine et al [13] first proposed an ACO-based solution for bin packing problem combined with a local search algorithm. Later, Brugger et al [14] used a later version of the ACO metaheuristic that demonstrated superior performance over genetic algorithm for large problem instances.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Levine et al [13] first proposed an ACO-based solution for bin packing problem combined with a local search algorithm. Later, Brugger et al [14] used a later version of the ACO metaheuristic that demonstrated superior performance over genetic algorithm for large problem instances.…”
Section: Related Workmentioning
confidence: 99%
“…16) using a probabilistic decision rule (Eq. 15) [line [11][12][13][14][15][16][17][18][19][20][21][22]. If the current PM is fully utilized or there are no feasible VMs left to assign to the PM, a new empty PM is taken to fill in [line [14][15][16].…”
Section: Avvmc Algorithmmentioning
confidence: 99%
“…It uses the classical encoding scheme. [12] uses a hybrid ant colony optimization, inspired by Falkenauer's works. It does not individualize the items, they are designated by their size and not their index: S = (w i ) i∈N with w i the size of item i.…”
Section: State Of the Artmentioning
confidence: 99%
“…We specifically choose this method as its execution times are very fast, but yet it is still able to produce solutions of equal quality to those achieved by other well-known packing algorithms such as the hybrid grouping genetic algorithm of Falkenauer (1998) and the ant-based algorithm of Levine and Ducatelle (2003). The former attribute is particularly useful because of the extra time that is consumed in determining groups' membership of F, a task that inevitably has to be performed many times during a run.…”
Section: Algorithm Frameworkmentioning
confidence: 99%
“…1) is then applied to S and T . This is a modified version of a procedure previously used with the BPP (Falkenauer, 1998;Levine and Ducatelle, 2003;Lewis, 2009) and is based on the concepts of dominance, defined by Martello and Toth (1990b). The idea is that items are interchanged between groups in S and groups in T such that the number of items in each group in S remains the same or decreases, while the total size of the items within these groups increases.…”
Section: Algorithm Frameworkmentioning
confidence: 99%